La diffusion de la toponymie scandinave dans la Normandie ducale - François de Beaurepaire (Tabularia)
Behind scandinavian place names known by historians and linguists, some observations have to be formulated. Scandinavian appellatives can be seen in the ancient regional dialect (so, la londe, le londel, le thuit, le becquet, les hogues) and place names issued from it, may be noticeably later than viking settlement; it is the case for scandinavian person names included in places names and which have been used for several generations. Concerning the question of geographic diffusion of scandinavian place names, we observe they have been generally given to parishes or rural estates, which lost their Carolingian designations, whereas some minor names (rivers, hamlets) better survived. Last but not least, the question is the contrast between the affluence of viking place names and the small number of the evidences which have survived in the regional vocabulary.